Efforts of Islamic Boarding School Teachers in Forming the Independence of Santri in Dayah Darul Huda, Langsa City - Fakhrurrazi Fakhrurrazi; Saparuddin Rambe; Meutia Sari (Fenomena, 2023)
This research aims to identify efforts and factors that support and hinder the efforts made by Islamic boarding school caregivers to promote the independence of students in Dayah Darul Huda, Langsa City. This research is descriptive research using a qualitative approach. The subjects in this research were all Dayah caregivers and all students at Dayah Darul Huda. Data collection techniques used observation, interviews, and documentation. The results of this research show that the efforts of Islamic boarding school caregivers to form the independence of students in Dayah Darul Huda, Langsa City, are carried out with three efforts, namely providing independence programs such as providing learning to students and implementing mandatory study hours for students. The second effort is to supervise the independence program. Supervision is carried out directly by caregivers or indirectly, namely through administrators. The third effort is to provide supporting activities such as training and courses, community service or cleaning every Friday, practicing muhadharah in three languages, recitations, conversations in three languages, practicing qasidah, and repeating the book, supporting factors for the efforts of Islamic boarding school caregivers in forming the independence of students. There are three, namely closeness between caregivers and students, students' personalities that comply with applicable rules, are disciplined and honest, and a strong will from students to follow efforts to establish independence from caregivers. Meanwhile, the factors inhibiting the efforts of Islamic boarding school caregivers in forming student independence are limited time and energy. Secondly, some students are less consistent, including sleepy students, tired students, students who do not obey the applicable rules, and students in unstable moods.